Increasing Taxes on Tobacco in Low and Middle-Income Countries : Hurting or Saving the Poor? - Fuchs Tarlovsky, Alan (World Bank, Washington, DC, 2020)
Policy makers hesitate to increase tobacco taxes over concerns about taxes being regressive and potentially increasing poverty and inequality. This note summarizes a set of studies of the effects of raising tobacco taxes in 11 low and middle-income countries using an extended cost-benefit analysis (ECBA) and harmonized national household budget survey data and introduces the TOBACTAX Tool. The studies find that demand price elasticities for tobacco products are larger among lower-income households and that the poor receive the largest long-term gains from tobacco taxation. Tobacco taxes have progressive long-term effects due to lower medical expenses and added years of productive life, which contribute to poverty reduction in most countries studied. TOBACTAX Tool can help replicate such analyses elsewhere.